Psychometric Properties of the Indebtedness Scale (IS-R) in Spanish University Students - Bernabé-Valero, Gloria; Moret-Tatay, Carmen; Iborra-Marmolejo, Isabel; Blasco-Magraner, José Salvador (Frontiers in Psychology, 2019)
The importance of trait indebtedness in the context of the study of gratitude has been growing in recent years, since both constructs form complex dynamics in response to the reception of a gift. In this work, the disposition to feel indebtedness is studied, through analysis of convergence and divergence, exploratory and confirmatory analysis in the Spanish population, with the most used measurement instrument, i.e. The Revised Indebtedness Scale, IS-R. This scale depicted a four factor solution interrelated with a high consistency of content, which allows their labeling and describing. To do this, two samples of university students were selected; one of the sample sizes had 229 participants and the other 200 participants. Results also indicated good internal consistency described as follows: Debt for material aspects (α=.81), Self-sufficiency and discomfort in receiving help (α=..82), Moral self-demand in the reception of help (α=..83) and Debt in the receipt of gifts (α=..75). Furthermore, it was suggested that the relationships between gratitude and indebtedness are complex: on the one hand, all the indebtedness factors are inversely correlated with gratitude, such as the GQ5, although only Self-sufficiency and discomfort in receiving help and Debt in the receipt of gifts are such to a significant extent. However, the Interpersonal Gratitude scale of the G-20 depicted low correlations only with the Self-sufficiency and discomfort. The results are discussed in relation to the need for conceptual definition of the constructs in Positive Psychology.